Analisis Tingkat Kesehatan Pada Koperasi Bina Tani Jaya Di Desa Bukit Pariaman Kecamatan Tenggarong Seberang - Mulyani, Retno _ (EKONOMIA, 2019)
Health Level Analysis On The Bina Tani Jaya Cooperative at Desa Bukit Pariaman Kecamatan Tenggarong Seberang. Mardiana and Andi Indrawati.            Assessment of the level of health in cooperatives is very useful to provide an overview of the condition of the cooperative itself to parties concerned, especially for members of cooperatives and managers, in addition to knowing the level of health of the cooperative based on Ministerial Regulation so that cooperatives are more developed and developing and the objectives of cooperatives can be achieved .            The study aims to determine the health level of Bina Tani Jaya Cooperative in 2017 based on the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No. 14 / Per / M. KUKM / XII / 2009 concerning the aspects of capital, quality of productive assets, management, liquidity, efficiency, independence and growth as well as cooperative identity..             The results showed that the health level of the Bina Cooperative Tani Jaya in 2017 is in a fairly healthy category getting a score of 60,25 with details: (1) The capital aspect gets a score of 15,00 and is in the healthy category. (2) Aspects of earning asset quality get a score of 12,25 and are in the unhealthy category, (3) Management aspects get a score of 12,00 and are in the healthy category. (4) The efficiency aspect in average gets a score of 6,00 and is in a fairly healthy category. (5) The liquidity aspect gets a score 3,75 and is in a very unhealthy category. (6) The aspect of independence and growth gets a score of 3,75 and is in the no category healthy. (7) The identity aspect of the cooperative gets a score of 7,50 and is in the healthy category.